Compact Four-Port MIMO Antenna Using Dual-Polarized Patch and Defected Ground Structure for IoT Devices - Dat Tran-Huy; Cuong Do-Manh; Hung Pham-Duy; Nguyen Tran-Viet-Duc; Hung Tran; Dat Nguyen-Tien; Niamat Hussain (Sensors)
This paper presents a compact four-port multiple-input multiple-output (MIMO) antenna for Internet-of-Things (IoT) devices. As electronic IoT devices become smaller, MIMO antennas should also be compact for ease of integration and multi-port operation for a high channel capacity. Instead of using a single-polarized radiator, which increases the antenna size when scaling to a multi-port MIMO array, a dual-polarized radiator is utilized. This helps to achieve multi-port operation with compact size features. To reduce the mutual coupling between the MIMO elements, an I-shaped defected ground structure is inserted into the ground plane. The measured results indicate that the final four-port MIMO antenna with overall dimensions of 0.92 <semantics>λ</semantics>× 0.73 <semantics>λ</semantics>× 0.03 <semantics>λ</semantics> at 5.5 GHz can achieve an operating bandwidth of about 2.2% with isolation better than 20 dB and a gain higher than 6.0 dBi. Additionally, the proposed method is also applicable to a large-scale MIMO array.